In the Company of Gods: essays in memory of Günther-Dietz Sontheimer - Malik, Aditya (Manohar [u.a.], 2005)
Contributed articles on folk religion, bhakti, history and law; in the Indian context
Keywords: Aufsatzsammlung; Festschrift; Hinduismus